Limburg bestaat niet. Paradoxen van een sterke identiteit - A. Knotter (BMGN: Low Countries Historical Review, 2008)
Where is Limburg? The Paradoxes of a Strong Regional Identity Limburg is a good example of the tensions that exist in the Dutch provinces Limburg is a good example of the tension that exist in the Dutch provinces between administrative territoriality, regional identity and spatial functionality. Right up to the present day, strong regional sentiments have hampered territorial restructuring based on more rational or functional criteria. Limburg was formed in 1815, much later than the other Dutch provinces, from different territories on both sides of the river Meuse. After the Belgian Revolt (1830- 1839) it was divided into a western (Belgian) part and an eastern (Dutch) part. This is how the Dutch part of Limburg acquired its odd elongated shape.